Faktor Sosial Ekonomi dan Pengetahuan dengan Status Gizi Balita di Desa Srimartani Kecamatan Piyungan Bantul - Hariza Adnani; Ismawati Ismawati (STIKes Surya Global Yogyakarta, 2022)
Background of Study: Based on the data from Health Office Bantul District, in 2019 there were toddlers who have malnutrition of 6.3264% and 0.38% of poor nutrition based on Monitoring Status Nutritional (MSN) recapitulation in the Piyungan Health Center. Srimatani village was the highest village who has malnutrition, there were 55 toddlers. The purpose of this study is to determine the socio-economic factors associated with the toddler nutritional status in Srimartani Village, Piyungan District, Bantul Regency.Methods: This type of research was an observational study with a cross-sectional approach. The population in this study were 94 toddlers in Srimartani Village, Piyungan District, Bantul Regency. The sampling technique used total sampling. Analyzing data used chi square test.Results:. Socio-economic factors related to the nutritional status of toddlers in Srimartani Village, Piyungan District, Bantul Regency were education (χ2 value = 45,277,Asymp sig = 0.00), employment status (χ2 value = 84,298 Asymp sig = 0.00); and income with nutritional status of toodler (χ2 value value = 24,851,Astmp sig = 0.00). There was no correlation between knowledge and nutritional status of toodler.Conclusion: Socio-economic factors related to the nutritional status of toddlers in Srimartani Village, Piyungan District, Bantul Regency are education, employment status and income; Knowledge of parents of toddlers is related to the nutritional status of toddlers in Srimartani Village, Piyungan District, Bantul Regency.Keywords: nutritional status, knowledge, socio-economic factors